Health-promoting behaviors and social support of women of reproductive age, and strategies for advancing their health: Protocol for a mixed methods study - Baheiraei, Azam (BioMed Central, 2011)
BACKGROUND: Determining the health-promoting behaviors of women during the important period of reproduction provides valuable information for designing appropriate intervention programs for advancing women's health. There is no study on the health-promoting behaviors of women of reproductive age in Iran. Thus, the aim of this study is to explore these health-promoting behaviors for the purpose of developing comprehensive and culturally sensitive health advancement strategies for Iranian women. METHODS/DESIGN: This study has a sequential explanatory mixed methods design. The follow-up explanation model is used to elaborate the quantitative results by collecting qualitative data from participants who could best assist in elucidating the results. The study is conducted in two sequential phases. The first phase is a population-based cross-sectional survey in which 1350 Iranian women of reproductive age are selected by proportional random multistage cluster sampling of the 22 main municipal sectors of Tehran, Iran. Questionnaires are completed through a face-to-face interview. The second phase is a qualitative study in which participants are selected using purposive sampling in the form of extreme case sampling on the basis of health-promoting behavior scores. The qualitative phase is based on data collected from focus group discussions or individual in-depth interviews. A conventional qualitative content analysis approach is used, and the data are managed with a computer-assisted program. Women's health-promoting strategies are developed using the qualitative and quantitative results, a review of the related literature, and the nominal group technique among experts. DISCUSSION: The findings of this mixed methods sequential explanatory study, obtained using a culturally sensitive approach, provide insights into the health behavioral factors that need to be considered if preventive strategies and intervention programs are to be designed to promote women's health in the community.